PENYELESAIAN SENGKETA BATAS WILAYAH NEGARA MENURUT PERSPEKTIF HUKUM INTERNASIONAL - Komang Trisma Berlianthi Astary (Universitas Pendidikan Ganesha, 2022)
International Law is a set of rules consisting mainly of principles and rules of conduct that are binding between countries and are therefore generally adhered to in the relations of countries with each other. International law aims to establish order and justice in the international community. But behind the purpose of international law to establish order and justice among countries, in today's reality in various parts of the world there are still problems related to the territorial boundaries of countries. The vast territory of a country makes the area very important for a country. Based on international law, the territory of the country consisting of land, sea and air is one of the very important elements for the place where people settle and the government realizes sovereignty and applies its jurisdiction. So international law is expected by the community because the international community is not static, because of this matter International Law also develops in accordance with the development of society.